Highly Efficient Deep Blue Luminescence of 2-Coordinate Coinage Metal Complexes Bearing Bulky NHC Benzimidazolyl Carbene - Hamze, Rasha; Idris, Muazzam; Muthiah Ravinson, Daniel Sylvinson; Jung, Moon Chul; Haiges, Ralf; Djurovich, Peter I.; Thompson, Mark E. (Frontiers in Chemistry, 2020)
The structural, photophysical and electrochemical properties of three luminescent 2-coordinate coinage metal (i.e., M = Cu, Ag, Au) complexes bearing a sterically bulky benzimidazolyl carbene, 1,3-bis(2,6-diisopropylphenyl)-1-H-benzo[d]imidazol-2-ylidene (BZI), and carbazolide (Cz) as the anionic ligand were investigated. All the complexes emit in the deep blue region ( 430 nm) with relatively narrow spectra (full width at half maximum = 44 nm, 2,300 cm−1) characterized by vibronic fine structure in nonpolar media (methylcyclohexane at room temperature), and with high photoluminescence quantum yields (ΦPL > 80%) and radiative rate constants (kr 7.8 × 105 s−1). The luminescence is solvatochromic, undergoing a red-shift in a polar solvent (CH2Cl2) at room temperature that are accompanied by a decrease in quantum yields (ΦPL < 23%) and radiative rate constants (kr < 4.0 × 104 s−1), whereas the non-radiative rate constants remain nearly constant (knr 1.0 × 105 s−1). The radiative rate is controlled via thermally assisted delayed fluorescence (TADF) and temperature-dependent luminescence studies of the gold complex (AuBZI) in methylcyclohexane solution reveal an energy difference between the lowest singlet and triplet excited states of 920 cm−1. An organic light-emitting diode (OLED) fabricated using AuBZI as a luminescent dopant has an external quantum efficiency of 12% and narrow, deep-blue emission (CIE = 0.16, 0.06).